Film Screenings of the Hong Kong YMCA During the Anti-Japanese War (1931-1941) - ZHANG, Shilin (Journal of Research for Christianity in China (JRCC), 2025)
Since 1904, the Hong Kong YMCA has been screening films in its central clubhouse, both commercially for the YMCA’s own operations and for the benefit of the elite for "wholesome and useful entertainment" and civic education for YMCA members.After China entered the partial war of resistance against Japan, the Hong Kong YMCA continued the above two types of film projection while using film to raise funds for the national salvation cause and to serve the community, promoting the national spirit and cultivating sound modern citizens through the drama and film activities of children’s theater groups. After the outbreak of the Sino-Japanese War, the Hong Kong YMCA and the Guangzhou YMCA jointly formed the Guangdong-Hong Kong YMCA Military Service Corps and set up a film crew to go north with the Cantonese army and conduct mobile film screenings, bringing spiritual comfort to the soldiers and inspiring patriotic enthusiasm among the soldiers and civilians to go to the country together.